Social and Cultural Relations in Islamic Law in Javanese Context: KH. Bisri Musthofa’s Thoughts on Qur’an and Hadith Issues - Akmaluddin, Muhammad (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
From an epistemological perspective, the environment creates knowledge and meaning of life for society. Knowledge is used to achieve people’s goals and expectations. This article examines the epistemology of Islamic law in Indonesia, particularly on the north coast of Java, in the context of its social and cultural background. To that end, this study investigated the works of KH. Bisri Musthofa, namely Tafsīr al-Ibrīz li Ma’rifa Tafsīr al-Qur’ān al-’Azīz and al-Azwād al-Musṭafawiyya fī Tarjama al-Arba’īn al-Nawawiyya. Many have already discussed the works of KH. Bisri Musthofa, but only a few touch on the issue of Islamic law in these works. This study argues that cultural context influences the authors of qur’anic and hadith interpretations to negotiate their understanding of customs and traditions, including in Java. Thus, the understanding of Islamic sharia on the north coast of Java is not passive, imitative and follows the thinking in the Arabian peninsula. The interpretation of the Qur’an and the understanding of hadith in Java indicate an active, creative and sustainable negotiation process related to the reality of society, social and cultural. This process then reconciles the two sources of law, between religious texts and cultural and social realities, and between sharia and haqiqa. Reconciliation shows that Islamic law was in its epistemic space on the north coast of Java in the 20th century.